Kritik Pragmatisme Richard Rorty Terhadap Epistemologi Barat Modern - Kalumbang, Yuventia Prisca (Jurnal Filsafat "WISDOM", 2018)
This essay focuses on characteristic of pragmatism and its philosophical function in pragmatism milieu that has been improved by Richard Rorty. It dicussess Rorty’s famous book: Philosophy and the Mirror of Nature. In Rorty’s view, pragmatism is a new philosophy orientation that goes beyond modern Western epistemology tradition. Epistemology in Western tradition since the 16-17 Century have been deeply influenced by Descartes, Locke and Kant, who spent great effort in stipulating all formal a priori categories as foundational constitutive factors of human knowledge. Such fondational knowledge is believed to represent reality and creates abstract-apriori and contemplation world. Instead of contemplation, Rorty pragmatism suggests a reverse way of knowing by introducing to the virtue of human’s concrete dimension which is united with dimension of action. In other words, understanding Rorty’s characteristic of pragmatism the same way to understand his critics against modern Western epistemology which has only created an abstract world and contemplation. The paper offers three parts of discussions; firstly, Rorty’s view on modern Western epistemology; followed by general characteristic of Rorty’s pragmatism, and last, its consequence toward philosophy function. Through pragmatism, Rorty affirms his support to plurality of human values and interest as concrete subject.